2024
DOI: 10.1038/s41598-024-54523-w
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol mitigates reproductive dysfunctions induced by Naja nigricollis venom through antioxidant system and anti-inflammatory response in male rats

Akindele Oluwatosin Adeyi,
Babafemi Siji Ajisebiola,
Akanni Abubakar Sanni
et al.

Abstract: Naja nigricollis Venom (NnV) contains complex toxins that affects various vital systems functions after envenoming. The venom toxins have been reported to induce male reproductive disorders in envenomed rats. This present study explored the ameliorative potential of kaempferol on NnV-induced male reproductive toxicity. Fifty male wistar rats were sorted randomly into five groups (n = 10) for this study. Group 1 were noted as the control, while rats in groups 2 to 5 were injected with LD50 of NnV (1.0 mg/kg bw;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Studies have reported the anti-inflammatory, antiapoptotic, antioxidative properties of kaempferol in vital organs, with possible mechanism via suppression of oxidative stress, inflammatory and apoptosis responses [35][36][37]. In addition, kaempferol is reported to have excellent anti-inflammatory and strong antioxidant activities via scavenging excessive ROS and preserving the intrinsic antioxidant enzyme activities at normal levels [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the anti-inflammatory, antiapoptotic, antioxidative properties of kaempferol in vital organs, with possible mechanism via suppression of oxidative stress, inflammatory and apoptosis responses [35][36][37]. In addition, kaempferol is reported to have excellent anti-inflammatory and strong antioxidant activities via scavenging excessive ROS and preserving the intrinsic antioxidant enzyme activities at normal levels [38][39][40].…”
Section: Discussionmentioning
confidence: 99%